Anti-biofilm activity of antibody directed against surface antigen complement receptor 3-related protein—comparison of Candida albicans and Candida dubliniensis. Issue 1 (5th January 2018) - Chupáčová, Jaroslava; Borghi, Elisa; Morace, Giulia; Los, Agata; Bujdáková, Helena
Abstract: Candida albicans and C. dubliniensis are related yeasts that differ in the expression of virulence-associated proteins involved in adherence and biofilm development. CR3-RP (complement receptor 3-related protein) is one of the surface antigens expressed by Candida species. The main objective of this research was to elucidate the effect of the polyclonal anti-CR3-RP antibody (Ab) on adherence and the biofilm formed by C. albicans SC5314 and C. dubliniensis CBS 7987 and two clinical isolates in vitro, ex vivo and in vivo . A comparison of species, and of treated vs. non-treated with the anti-CR3-RP Ab showed a reduction in adherence (22%–41%) that was dependent on the time point of evaluation (60, 90 or 120 min), but did not prove to be species-dependent. Confocal microscopy revealed a decreased thickness in biofilms formed by both species after pre-treatment with the anti-CR3-RP Ab. This observation was confirmed ex vivo by immunohistochemistry analysis of biofilms formed on mouse tongues. Moreover, anti-CR3-RP Ab administration, 1 h post-infection, has been shown to promote larval survival compared to the control group in a Galleria mellonella infection model. Our data suggest a potential activity of the anti-CR3-RP Ab relevant to immunotherapy or vaccine development against biofilm-associated Candida infections. Abstract : Antibody directed against complement-receptor 3 related protein (CR3-RP) interfere with biofilm formation in Candida albicans and Candida dubliniensis.